Is the Ordos Block Archean or Paleoproterozoic in age? Implications for the Precambrian evolution of the North China Craton - Wan, Yusheng; Xie, Hangqiang; Yang, Hua; Wang, Zejiu; Liu, Dunyi; Kröner, Alfred; Wilde, Simon; Geng, Yuansheng; Sun, Liuyi; Ma, Mingzhu; Liu, Shoujie; Dong, Chunyan; et al. (American Journal of Science, 2013)
The Ordos Block is a large but poorly exposed crustal segment in the western part of the North China Craton. Little is known about its Precambrian basement rocks and their evolution because of an extensive cover by younger sedimentary rocks. We report SHRIMP zircon ages and Hf-in-zircon isotopic compositions for five samples recovered from drill holes that penetrated into the Ordos basement. Based on these data, two age groups of rocks can be distinguished: an early Paleoproterozoic group that is represented by one sample from the northern margin of the Ordos Block and a late (or middle-late) Paleoproterozoic group consisting of the remaining four samples. The early Paleoproterozoic sample contains zircon cores and metamorphic rims with ages of >2.4 Ga and >2.28 Ga, respectively. The cores have εHf(t) values of −8.8 to 6.2 and Hf crustal model ages of 2606 to 3221 Ma.The remaining rocks of late (or middle-late) Paleoproterozoic age contain zircons that may also show a core-rim structure, but with the cores having ages of ~2.08 Ga and the metamorphic rims recording ages of ~1.9 Ga. The zircon cores have εHf(t) values of −9.1 to 10.1, and Hf crustal model ages of 2039 to 3068 Ma. Combined with data from earlier studies, we draw the conclusion that late Paleoproterozoic metasedimentary rocks are widespread in the Ordos basement. There is no evidence from our samples of an Archean component, and this calls into question the prevailing view that the Ordos basement is an Archean cratonic block. The fact that the Ordos basement was involved in a widespread late Paleoproterozoic tectono-thermal event indicates that most current models for the tectonic evolution of the western portion of the North China Craton need to be revised.